Youths Blossom at Laventille Pan Festival - Blood, Peter Ray (Trinidad Guardian)
The artistic entities of the Laventille Police Youth Club and the Laventille Rhythm Section brought pride to the community when they participated in the 2012 Laventille Emancipation Steelband Festival.
Keywords: Youth -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Music festivals -- Trinidad and Tobago